Application of Financial Reporting Based on SAK EMKM in Micro Enterprises : A Case Study of Catfish Farming “Barokah” in Sugih Waras, Indonesia - Jayus Amirullah Parera; Adiati Trihastuti (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study investigates the implementation of the Indonesian Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in improving financial management in micro-enterprises. The case study focuses on the “Barokah” catfish farming business in Sugih Waras Village, Magetan, East Java. Using a qualitative descriptive method involving interviews, observation, and documentation, the study found that the enterprise initially lacked structured financial documentation. Through targeted mentoring, the business owner was able to develop financial reports compliant with SAK EMKM, leading to enhanced financial literacy, accountability, and business credibility. The study underscores the importance of SAK EMKM in promoting financial inclusion and sustainability among micro-enterprises in rural Indonesia.